KEEFEKTIFAN MODEL PROBLEM BASED LEARNING BERBANTU MEDIA BIG BOOK TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI IPAS BAGIAN TUBUH TUMBUHAN KELAS IV SD NEGERI 04 JATINGARANG PEMALANG - Yulistyas, Nikken; Wijayanti, Arfilia; Sulianto, Joko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigated the effectiveness of Problem Based Learning (PBL) supported by Big Book media to improve fourth-grade students’ IPAS learning outcomes on plant body parts at SD Negeri 04 Jatingarang, Pemalang. Using a one-group pretest–posttest design with 18 students, data were collected through cognitive tests and observations of affective and psychomotor domains across three meetings. Results showed the mean score increased from 54.17 to 87.66 with an N-gain of 67.60% (moderately effective), while mastery learning rose from 25% to 62.5%. Affective and psychomotor scores also improved (76.67 → 90.00 → 96.67). Overall, PBL with Big Book media effectively enhanced learning outcomes and supported students’ attitudes and skills.